A Fast, Analytically Based Method to Optimize Local Transmit Efficiency for a Transmit Array - Carluccio, Giuseppe (2013)
PURPOSE: To develop an analytically based algorithm for rapid optimization of the local radiofrequency magnetic ( [Formula: see text]) field intensity for a given radiofrequency power through a transmit array. The analytical nature of the method will yield insight to optimization requirements and provides a valuable reference for numerically based searches. METHODS: With the knowledge of the [Formula: see text] field distribution generated by each single coil of the array, both the phases and the amplitudes of each coil current are optimized to maximize the magnitude of the [Formula: see text] field in a specific location of the body per unit of power transmitted through the array and, consequently, minimizing the whole body specific absorption rate for a given pulse sequence. RESULTS: Simulations considering the human body show that the proposed method can reduce the whole-body specific absorption rate for a given [Formula: see text] magnitude at the location of interest by a factor of about 6.3 compared to the classic birdcage current configuration, and by a factor of 3.2 compared to phase-only shimming in a case with significant coupling between the elements of the array. CONCLUSION: The proposed method can rapidly provide valuable information pertinent to the optimization of field distributions from transmit arrays.